Recognition and Modeling of Crisis Propagation Patterns Combined with Robot Simulation of Social Networks - Yafei Wang (Journal of Robotics)
In order to improve the identification effect of a crisis propagation mode, this paper studies the crisis propagation mode of social networks and uses an intelligent method to identify the crisis propagation mode. Moreover, this paper analyzes and deduces the features of the modulated signal from the two aspects of spectrum and autocorrelation functions and extracts and simulates the features of signals of different modulation types. In addition, this paper verifies the proposed recognition method from two aspects through theoretical experiments and measured data and builds an intelligent model. Through the experimental research, it can be seen that the identification effect and the control effect of the crisis propagation model based on the social network proposed in this paper are relatively obvious.